Numerical Simulation on Impact Test of CFRP Strengthened Reinforced Concrete Beams - Qingfeng, He; Jiang, Li; Leiyang, Yue; Jiawei, Mao (Frontiers in Materials, 2020)
As the main horizontal load-bearing member, the research on the impact resistance of reinforced concrete beams is an important part of the design of building structures against strong dynamic loads. Therefore, impact-resistant design is critical to the safety and maintainability of such structures. However, the impact performance of RC beams has not been well understood, and the methods of strengthening RC structures to resist impact loads are still very limited. In this study, experimental tests and numerical simulations were carried out to study the performance of RC beams with or without FRP reinforcement under impact loads. In order to study the dynamic performance of reinforced concrete beams before and after CFRP reinforcement under different impact conditions, the finite element analysis software ANSYS/LSDYNA was used to simulate the impact test of five ordinary RC beams and five strengthened beams. The impact speed and impact weight of the drop hammer are mainly changed during the simulation, and the stress distribution, crack development and failure morphology, and CFRP resistance contribution of the specimen were analyzed. The simulation results show that CFRP can alleviate the high stress in the impact transient concrete, reduce the deformation of the beam body, limit the crack development, and provide a certain impact resistance. The increase of the impact height has a more significant effect on the transient response of the component. CFRP can effectively restrain the deformation under different impact weight conditions. Therefore, strengthening RC beams with CFRP is an effective method to improve the impact load resistance.